Sexual violence as a factor contributing to adolescent pregnancy in lower middle-income countries: a systematic review - Kumar Jha, Shivam; Akhtar, Rashid; Khan, Salman (International Journal Of Community Medicine And Public Health, 2025)
Adolescent pregnancy, particularly unintended, is influenced by multiple factors at individual, community, and societal levels. According to the WHO, 95% of adolescent pregnancies occur in low- and middle-income countries, with a majority being unintended. Sexual violence is one of the keys, yet underexplored, contributors to such pregnancies. This systematic review aimed to explore the association between sexual violence and adolescent pregnancy in lower-middle-income countries, as classified by the World Bank. The literature search was conducted using the terms “Adolescent Pregnancy” AND “Sexual Violence” across PubMed and Google Scholar. Out of 1001 articles identified, five peer-reviewed studies met the inclusion criteria and were analyzed. Findings revealed that most first pregnancies among adolescents were unintended and often linked to sexual violence, including forced sex, coercion, or rape. The COVID-19 pandemic, with its related lockdowns and school closures, has further increased adolescent girls’ vulnerability by deepening poverty and limiting access to sexual and reproductive health (SRH) services. All studies emphasized the urgent need for poverty reduction strategies, improved access to SRH services, and comprehensive sexuality education. Empowering adolescent girls with knowledge and resources to protect themselves from sexual abuse and coercion is critical. Policymakers must prioritize interventions that address gender inequalities and strengthen protection mechanisms against sexual violence to prevent unintended adolescent pregnancies.